2018
DOI: 10.1021/acsomega.8b02744
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Zigzag and Armchair Edges on Graphene Nanoribbons by X-ray Photoelectron and Raman Spectroscopies

Abstract: Graphene nanoribbons (GNRs) have recently emerged as alternative 2D semiconductors owing to their fascinating electronic properties that include tunable band gaps and high charge-carrier mobilities. Identifying the atomic-scale edge structures of GNRs through structural investigations is very important to fully understand the electronic properties of these materials. Herein, we report an atomic-scale analysis of GNRs using simulated X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy. Tetracene with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 43 publications
2
43
0
Order By: Relevance
“…Table 1 shows the calculated gap between HOMO and LUMO of the GNFs with or without heptagons. It has been reported that the HOMO–LUMO gap increases with decreasing the size of graphene 31 and introducing heptagons in graphene. 33 As shown in Table 1 , the HOMO–LUMO gap of the GNF with zero heptagons was 0.80 eV, which decreased to 0.23 eV when four isolated heptagons were introduced, as the size of GNF and the number of isolated heptagons increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the calculated gap between HOMO and LUMO of the GNFs with or without heptagons. It has been reported that the HOMO–LUMO gap increases with decreasing the size of graphene 31 and introducing heptagons in graphene. 33 As shown in Table 1 , the HOMO–LUMO gap of the GNF with zero heptagons was 0.80 eV, which decreased to 0.23 eV when four isolated heptagons were introduced, as the size of GNF and the number of isolated heptagons increased.…”
Section: Resultsmentioning
confidence: 99%
“…The binding energy associated with the C1 region was higher than that associated with the C2 region because the terminal hydrogen atoms donate electrons to the carbon atoms (C2). 16 , 28 , 29 , 31 The binding energy associated with the C3 region (indicated by two isolated heptagons in the GNF structure) was 284.7 eV (yellow line in Figure 3 b), which was the highest binding energy among the C1, C2, and C3 regions owing to the electron-donating nature of the heptagons ( Figure S1 ). All the structures used in this study showed the same tendency ( Table 2 and Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group demonstrated the peak shifts and the corresponding full widths at half-maximum (fwhms) of the XPS peaks of nanocarbon materials with various defects. 39 , 41 − 43 The XPS peak originating from vacancy defects appears at ±0.7 eV from the C=C and/or C–H main peak. 39 , 41 Thus, the fwhm of the peak originating from the C=C and/or C–H peak increased upon the introduction of internal pores to the CNT wall due to the presence of an increased number of vacancies and edge structures in the wall.…”
Section: Resultsmentioning
confidence: 99%
“… 39 , 41 − 43 The XPS peak originating from vacancy defects appears at ±0.7 eV from the C=C and/or C–H main peak. 39 , 41 Thus, the fwhm of the peak originating from the C=C and/or C–H peak increased upon the introduction of internal pores to the CNT wall due to the presence of an increased number of vacancies and edge structures in the wall. 39 , 41 However, the fwhm of the peak originating from the C=C and/or C–H moiety of the HD-SWCNT film was not increased compared to that of the SWCNTs ( Figure 2 c), which indicates either that the number of internal pores was small or that no internal pores were introduced.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the graphene tension was carried out for two basic directions (if the edge is cut-out along bonds between carbon atoms, one receives the “armchair” edge, otherwise the cutting-out in the perpendicular direction has the edge called “zigzag” [49]).…”
Section: Assumptions For Modeling the Graphene Structurementioning
confidence: 99%